Penggunaan Model DeLone Dan McLean Dalam Mengukur Kesuksesan Aplikasi Go-Jek Di Palembang - Erwin erwin; Andri Wijaya (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
Go-jek application is an online transportation application by the children of the nation which has caused many phenomena since it was first launched. Based on "8 Go-Jek Flashback Notes 2018", we can see the phenomenon that occurs, this shows the important role of the Go-Jek application, both in supporting the development of Go-Jek and in facilitating the community to use Go-Jek services. Therefore this research was conducted to scientifically measure the success of Go-Jek applications by using the Information System Success Model (ISSM) proposed by DeLone and McLean. The sampling technique used in this study was purposive sampling, with a total sample of 100 people through a questionnaire to get research data to be analyzed using multiple linear regression analysis with the results of 12 hypotheses formulated, 9 hypotheses proved to be significant, this makes the application go can be categorized as a good system. While the other 3 hypotheses are insignificant, which means that go-jek application users in Palembang community assume the quality of information and the quality of the existing system in go-jek applications do not affect the satisfaction they expect and the quality of the system does not become their judgment in using go-jek applications.